Competition law in Malaysia: issues and challenges in regulating market behaviour - Ambaras Khan, Mushera Bibi; Abdul Rahman, Nasarudin; Alavi, Rokiah; Ahamat, Haniff (2013)
The fundamental objective of competition law is to protect the process of rivalry between firms in the market. It prohibits any anti-competitive behaviour such as cartel, abuse of dominant position and mergers that have the effect of lessening competition. However, in practice regulating firms' behaviours in the market is not an easy task. It requires both legal and economic analysis to determine which conducts are or are not allowed under the competition law regime. This paper seeks to identify and analyse the important provisions of "anti-competitive agreements" and "abuse of dominant position" under the Malaysian Competition Act 2010 (CA). It is observed that the CA has been heavily influenced by the UK and EU competition law. Despite the similar concepts applied, the actual implementation of the law may differ. This paper seeks to explore the issues and challenges that the Malaysian competition authority might be facing in enforcing competition rules which are largely drawn from foreign ideas.